Performance Analysis of AODV Routing Protocol Using Different Directional (Metamaterial) Antenna in MANET (International Journal of Communication Systems and Network Technologies, 2015)
In this paper a comparative study is represented of different directional metamaterial antennas in mobile ad-hoc network using ad-hoc on demand distance vector (AODV) routing protocol. Complexity of routing is increasing between mobile nodes as number of users increasing because of dynamic nature of mobile nodes and rapid change in mobile topologies in mobile ad-hoc networking. However, it is possible to improve the network congestions by using the directional antenna. We use directional antenna because of good directivity. To find out which directional antenna gives better result for mobile ad-hoc networks (MANET), in the paper, we simulate the scenario of three different directional antenna for comparing and analyzing using routing protocol such as AODV, using QualNET simulator 6.01. The metrics used for performance evaluation and comparison of different metamaterial antennas using routing protocol AODV, we are going to compare throughput, average unicast end to end delay, unicast jitter and physical layer metrics is received power of receiving node.
Keywords: Ad-hoc Network; AODV; Directional Antenna; Metamaterial; QualNet